Strategi Pendidikan Karakter terhadap Perubahan Sosial Keagamaan Masyarakat Pegunungan Kalibawang Yogyakarta - Ahmad Salim; Mohamad Ardin Suwandi (Yayasan Azhar Amanaa Yogyakarta, 2023)
The emergence of intolerant behavior between religious communities is a reality that can tear apart the harmony of society, especially what happened in Kalibawang Kulon Progo, Yogyakarta. MAN 3 Kulon Progo is aware of this reality by implementing several strategies in response to the phenomenon of intolerance that occurs. This study describes MAN 3 Kulon Progo's strategy to internalize tolerant behavior in madrasah students. Data collection was done through observation and in-depth interviews with selected respondents and supported by Berger's social construction theory and Lickona's on the stages of character internalization, namely moral knowledge, moral love and moral action. The results showed that the strategy of inculcating tolerant behavior was carried out in 2 ways, namely within the madrassah and activities outside the madrasah that were directly in contact with the community at large. This activity is able to build students to have a tolerant attitude as a basis for the harmonization of community life can be created